40/30 – 40 years of Constitution, 30 years of European integration: between past and present, openness and belonging - Canotilho, Mariana (2017)
This paper reflects about the Portuguese constituent process, within the framework of the so-called constitutionalism of the Social State, typical of European countries, during the second half of the 20th century. It also aims at understanding European integration from a constitutional point of view, having in mind the unusual openness of the Constitution of the Portuguese Republic to foreign legal orders. The analysis confronts the processes of constitutionalization and integration, and it defends that several elements of the first one should be incorporated into the latter.